Predictive factors based on the health belief model on cancer screening behaviour in first degree relatives of patients with Lynch syndrome-associated colorectal cancer - Jiaojiao Gu; Shumin Jia; Huaxiang Chao; Tinglan Chen; Xiaodan Wu (Elsevier, 2023)
Objectives: This study aimed to investigate colorectal cancer-related knowledge, health beliefs, and screening behaviour in first-degree relatives (FDRs) of patients with Lynch syndrome-associated colorectal cancer (CRC) and explore the predictive factors of screening behaviour based on a health belief model. Methods: This cross-sectional study was conducted in the colorectal department of a Class A tertiary hospital in Guangzhou from December 2017 to December 2019. A total of 265 FDRs of 96 patients with Lynch syndrome-related CRC were selected. The study was conducted in the colorectal department of a tertiary cancer centre in Guangzhou. The demographic questionnaire, the simplified CRC knowledge questionnaire, and the Champion's Health Belief Model Scale were used for evaluation. Data were analyzed using statistical description, between-group comparisons, and binary logistic regression. Results: A total of 160 (60.4%), 61 (23.0%), and 44 (16.6%) of the participants had high, medium, and low levels of knowledge about CRC, respectively; the average overall score of health belief was 121.36 ± 13.02. Sixty-one participants (23.0%) underwent Lynch syndrome-associated cancer screening. The predictive factors of screening behaviour included sex (male), age (older), married status (married), multiple primary cancers of the index patients, and high levels of knowledge and health beliefs (P < 0.05). Conclusions: The knowledge and health beliefs of cancer and cancer screening in FDRs of patients with Lynch syndrome-associated CRC should be improved. Both knowledge and beliefs are critical in promoting their cancer screening behaviour. Interventions should focus on health education and enhance health beliefs of the FDRs for better screening behaviour.